Perancangan Dimensi Sump di PT. Satria Alam Manunggal Site Telen Orbit Prima Desa Buhut Kecamatan Kapuas Tengah Kabupaten Kapuas Kalimantan Tengah - Sri Rahmawati; Noveriady Noveriady; Yunida Iasahnia; Neny Fidayanti; Asri Fridtriyanda (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study aims to evaluate the actual sump capacity in accommodating mine water discharge, design a sump that fits field conditions, and determine the optimal pump capacity and system at PT Satria Alam Manunggal, Telen Orbit Prima Site. The research methods include field data collection (sump condition, water discharge, and pump capacity) and supporting data (rainfall, geological maps, and pump specifications). The design rainfall was calculated using the Gumbel method with a five-year return period, while water discharge was estimated from runoff, rainfall, and groundwater inflow. The results indicate that the existing sump, with a capacity of 508 m³, is insufficient to accommodate an inflow of 1.210 m³/s. Therefore, two new sumps were designed: the West Sump with a capacity of 38,400 m³ and the East Sump with 78,281 m³. Each sump employs a DnD 150-4H pump with a discharge rate of 480 m³/hour. The West Sump pump can drain water within approximately three days, while the East Sump requires about seven days. The trapezoidal sump design was chosen for its efficiency, structural stability, and effectiveness in sediment (TSS) deposition control, maintaining levels within safe limits. In conclusion, the design of the West and East sumps is considered optimal in accommodating mine water discharge and improving the overall effectiveness of the mine drainage system.